Histone deacetylases: the critical enzymes for microglial activation involved in neuropathic pain - Ding, Yi (Frontiers in Pharmacology, 2025)
Neuropathic pain is a common health problem in clinical practice that can be caused by many different factors, including infection, ischemia, trauma, diabetes mellitus, nerve compression, autoimmune disorders, cancer, trigeminal neuralgia, and abuse of certain drugs. This type of pain can persistently affect patients for a long time, even after the rehabilitation of their damaged tissues. Researchers have identified the crucial role of microglial activation in the pathogenesis of neuropathic pain. Furthermore, emerging evidence has shown that the expression and/or activities of different histone deacetylases (HDACs) can modulate microglial function and neuropathic pain. In this review, we will summarize and discuss the functions and mechanisms of HDACs in microglial activation and neuropathic pain development. Additionally, we will also list the emerging HDAC inhibitors or activators that may contribute to therapeutic advancement in alleviating neuropathic pain.